Social engineering: the weakest link of safety in companies (Revista Brasileira de Contabilidade e Gestão, 2012)
The technology shows up as a success factor for many companies. Upgrade equipment and security systems demand much attention and knowledge of the area. Even with an upgraded security system companies still face a big problem detected for some years on the market: vulnerability to social engineering attacks, professionals seeking to break the security technology for their own gains. This work aims to question whether people who manipulate such systems possess attributes to make it as best as also inform all stakeholders that security goes beyond the equipment and the human ability to persuade the next to get what you want can bring great harm. Social engineering may be the weakest link in the security of sensitive information and data.
Keywords: social engineering; people; security; system; technology